Cellular uptake mechanisms and toxicity of quantum dots in dendritic cells. (July 2011) - Zhang, Leshuai W; Bääumer, Wolfgang; Monteiro-Riviere, Nancy A
Quantum dots (QDs) are nanoparticles with strong fluorescent emission and are novel tools used in biomedical applications, but the toxicity and mechanism of cellular uptake are poorly understood. QD655-COOH (negative charge, 18 nm) consist of a cadmium/selenide core and a zinc sulfide shell with a carboxylic acid coating with an emission wavelength of 655 nm.Materials & Methods: Peripheral blood mononuclear cells were isolated from porcine blood by gradient centrifugation, and monocytes, which are CD14 positive, were purified. Monocytes were differentiated into dendritic cells (DCs) with GM-CSF and IL-4.Results: Monocytes showed cellular uptake of QD655-COOH, while lymphocytes did not. Monocyte differentiation into DCs increased the cellular uptake by sixfold when dosed with 2 nM of QD655-COOH. Transmission electron microscopy depicted QD655-COOH in the cytoplasmic vacuoles of DCs. Twelve endocytic inhibitors demonstrated QD655-COOH endocytosis in DCs, which was recognized by clathrin and scavenger receptors and regulated by F-actin and phospholipase C. In addition, DC maturation with lipopolysaccharide (LPS) caused an increase in QD655-COOH uptake compared with DCs without LPS stimulation. Viability assays, including 96AQ, CCK-8, alamar blue and ApoTox, exhibited minimal toxicity in DCs dosed with QD655-COOH at 24 h. However, glutathione levels showed a significant decrease with 10 nM of QD655-COOH. Finally, QD655-COOH exposure was associated with a decrease in CD80/CD86 expression after LPS stimulation, suggesting suppression with DC maturation.Conclusion: These findings shed light on the mechanism of QD655-COOH uptake in DCs and that cellular uptake pathways are dependent on cell type and cell differentiation.